Electric autonomous vehicles in shared ownership : perceptions of swedish consumers - Eriksson, Karl David (2022)
Due to the vehicular trends over the last decade, it becomes more and more evident that the future of mobility is electric. According to The European Environment Agency (2020) penetration of electric vehicles are already growing in all European countries and Goldman Sachs (2021) predicts that in 2025, 25% of all cars sold will be EVs, 70% in 2030, 80% in 2035 and 95% in 2040. At the same time of electrification of vehicles, many scholars and experts agree that autonomous vehicles will play a significant role in the future generation of mobility. Additionally with the increasing usage of carpools and shared mobility, a future business model that combines electric autonomous vehicles with shared ownership of cars could drastically disrupt and change the industry. This thesis investigates the case for Sweden, how consumers perceive such a business model. With a consumer survey and interviews with experts in the field, the thesis aims to give insights into what perceived barriers exists for Swedish consumers to participate in said business model, and what inflection points exists for them to overcome their perceived barriers. The paper found already existing issues regarding owning electric vehicles the most powerful ones - limited charge points and price. Further, the main inflection point to overcome the barriers and participate in said shared, electric & autonomous carpool is economic.